Dari Tradisional Menuju Fungsional: Analisis Sensori Putu Ayu Original vs. Putu Ayu Substitusi Tepung Daun Kale - Aulia, Wahyu Mafatikhul; Rahma Hafida; Azis Nur Rosyid (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The purpose of this study is to analyse the comparison of sensory characteristics between original putu ayu cake and a variant with a 25% substitution of kale leaf flour. The substitution of kale leaf flour is expected to serve as a natural alternative for coloring while also improving the cake's nutritional value. This research utilized a quantitative experimental approach, involving organoleptic testing with 62 panelists from the Brangsong Baru Housing. The panelists evaluated four sensory aspects: aroma, color, taste, and texture. The results from the organoleptic tests showed that substituting kale leaf flour positively influenced the aroma of the putu ayu cake without compromising its texture. However, the color and taste still require improvements to enhance the overall consumer acceptance of the cake. These findings highlight the potential of kale leaf flour as a functional ingredient in traditional cakes, offering a healthier alternative while maintaining the sensory qualities that consumers expect.